PERAN JOB INSECURITY DAN SISTEM KERJA KOMITMEN TINGGI TERHADAP KESEJAHTERAAN KARYAWAN - Nanda Satria; Unggul Kustiawan (JURNAL CAFETARIA, 2023)
This study aims to determine how significant the role and influence of job insecurity, trust in the organization, and work system is in a high commitment to employee welfare in millennial employees. Many people feel the uncertainty, confusion, and fear caused by COVID-19, primarily due to the failure of the current system to provide employee health and welfare. Data collection in this study used a survey method that was distributed online in 2022, and respondents were selected using the purposive sampling method for millennial workers with a total of 213 millennial employees, the analysis in this study was factor analysis and structural modeling (SEM). This research shows that belief in the organization and work system of high commitment can affect employee welfare, but job insecurity has no relationship with employee welfare, so it is necessary to consider the role of work insecurity in millennial employees in influencing and welfare of their employees, this is due to an outbreak or the effect the COVID-19 pandemic which still exists today and is still very much felt.